2004
DOI: 10.1295/polymj.36.96
|View full text |Cite
|
Sign up to set email alerts
|

Sterically Stabilized Emulsion Polymerization of Styrene

Abstract: ABSTRACT:Batch emulsion polymerizations of styrene initiated by ammonium peroxodisulfate (APS) and 2,2 0 -azobisizobutyronitrile (AIBN) at a broad monomer concentration range were investigated. The role of the thick emulsifier layer formed by a nonionic emulsifier was investigated in the sterically stabilized emulsion polymerization of styrene. The polymerization rate vs. conversion dependence was characterized by two or three nonstationary rate intervals. The rate of polymerization increases with the monomer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…[ 12 ] Although the vast majority of these polymerizations are thermally initiated, an alternative approach was UV light induced the polymerization from monomer microemulsion. [13][14][15][16] More recently miniemulsions [17][18][19] composed of metastable acrylate nanodroplets ( < 100 nm) with weakly scattering properties are prepared in water permitting a suffi cient penetration of light. Nucleation is assumed to take place inside nanodroplets and promote their conversion into polymer particles, in the absence of any destabilization phenomena.…”
Section: Photopolymerization In a Photoreactormentioning
confidence: 99%
“…[ 12 ] Although the vast majority of these polymerizations are thermally initiated, an alternative approach was UV light induced the polymerization from monomer microemulsion. [13][14][15][16] More recently miniemulsions [17][18][19] composed of metastable acrylate nanodroplets ( < 100 nm) with weakly scattering properties are prepared in water permitting a suffi cient penetration of light. Nucleation is assumed to take place inside nanodroplets and promote their conversion into polymer particles, in the absence of any destabilization phenomena.…”
Section: Photopolymerization In a Photoreactormentioning
confidence: 99%
“…The kinetics of inverse miniemulsion polymerization and copolymerization of acryalmide was reported by Capek et al [19][20][21][22][23][24]. The conversion-time data for the inverse miniemulsion polymerization of acrylamide initiated by ammonium peroxodisulfate (APS) at different emulsifier (Tw 85) concentrations are shown in Figure 8.1 [21].…”
Section: Kinetic Studiesmentioning
confidence: 91%
“…The conversion-time data for the inverse miniemulsion polymerization of acrylamide initiated by ammonium peroxodisulfate (APS) at different emulsifier (Tw 85) concentrations are shown in Figure 8.1 [21].…”
Section: Kinetic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a few studies have been reported by several authors [26][27][28], this technique will not be detailed herein. low practical value (Scheme 13.8).…”
Section: Photoinduced Grafting Methodsmentioning
confidence: 99%